1996
DOI: 10.1007/s002040050366
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase GSTM1 and GSTT1 null genotypes as potential risk factors for urothelial cancer of the bladder

Abstract: One-hundred-and-thirteen patients with cancer of the urinary bladder (cases) were examined with respect to the frequency of null genotypes of the polymorphic glutathione S-transferases GSTM1 and GSTT1. The allelic background in the German population of the area was evaluated by analysing 170 newborns (controls). The frequency of GSTM1 and GSTT1 null genotypes in this population, using methods based upon internal standard controlled polymerase chain reaction (PCR), was 0.54 and 0.18 respectively. An elevated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
7

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 0 publications
6
42
0
7
Order By: Relevance
“…Association of the GSTP1 313 A/G or G/G genotypes with bladder cancer in the Turkish population is in accord with ®ndings in the British population ), but not with those in the Japanese (Katoh et al 1999) or German (Steinho et al 2000) populations. The lack of association between bladder cancer and the GSTT1 locus is in agreement with studies in the Greek (Georgiou et al 2000) and German (Kempkes et al 1996;Steinho et al 2000) populations, but not with results for Slovaks (Salagovic et al 1999). Bladder cancer is a malignancy in which, in addition to the genetic status of the individual, gene-environment interactions are thought to play an important role.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Association of the GSTP1 313 A/G or G/G genotypes with bladder cancer in the Turkish population is in accord with ®ndings in the British population ), but not with those in the Japanese (Katoh et al 1999) or German (Steinho et al 2000) populations. The lack of association between bladder cancer and the GSTT1 locus is in agreement with studies in the Greek (Georgiou et al 2000) and German (Kempkes et al 1996;Steinho et al 2000) populations, but not with results for Slovaks (Salagovic et al 1999). Bladder cancer is a malignancy in which, in addition to the genetic status of the individual, gene-environment interactions are thought to play an important role.…”
Section: Discussionsupporting
confidence: 81%
“…The valine amino acid results in decreased enzyme activity (AliOsman et al 1997). Despite this neat theoretical framework, the results of association studies between GST genotypes and bladder cancer are discordant in dierent populations (Bell et al 1993;Zhong et al 1993;Lin et al 1994;Anwar et al 1996;Brockmoller et al 1996;Kempkes et al 1996;Okkels et al 1996;Golka et al 1997;Harries et al 1997;Katoh et al 1999;Salagovic et al 1999;Georgiou et al 2000;Mungan et al 2000;Steinho et al 2000). Although methodological dierences might be partially responsible for this discrepancy, the risk might be speci®c for the studied population because of dierences in environmental factors, polymorphism frequencies and gene-gene interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Other independent studies on various types of cancer have also shown this relationship between XMEs and lung cancer (Lan et al, 2000), bladder cancer (Anwar et al, 1996;Kempkes et al, 1996), colorectal cancer (Deakin et al, 1996), breast cancer (Mitrunen et al, 2001), esophageal cancer (Van Lieshout et al, 1999), oral cancer (Nair et al, 1999), and leukemia .…”
Section: Authorsmentioning
confidence: 81%
“…Since UC is often associated with exposure to carcinogens, researchers have evaluated the use of the GST genotype for stratifying UC risk (Kempkes et al, 1996). Other studies have investigated either GST genetic polymorphisms or tissue-specific GST expression in bladder cancer (Giralt et al, 1993;Pljesa-Ercegovac et al, 2010;PljesaErcegovac et al, 2011).…”
Section: Discussionmentioning
confidence: 99%